Creating a new legal form: The GmbH - Timothy W. Guinnane; Jochen Streb (Yale University, Economic Growth Center, 2020)
The most common business enterprise form in Germany today is the Gesellschaft mit beschränkter Haftung (GmbH). The GmbH offers entrepreneurs the partnership's flexibility combined with limited liability, capital lock-in, and other traits associated with corporations. Earlier enterprise forms such as the partnership and corporation were codified versions of longstanding practice; the GmbH, on the other hand, was the lawgiver's creation. Authorized in 1892, the GmbH appeared during a period of ferment in German enterprise law and was an early example of the "Private Limited-Liability Company" (PLLC) prevalent in many economies today. This paper traces the debates and the legislative process that led to the GmbH's introduction. The new form reflected challenges created by the corporation reform of 1884, problems in German colonial companies, and the view that British company law had put German firms at a competitive disadvantage. Many new enterprises adopted the GmbH, but significant sections of the financial and legal community harbored strong reservations about this legal innovation.
Keywords: 330; Rechtsform; GmbH; Rechtsgeschichte; Deutschland (bis 1945)